POLA KOMUNIKASI NARAPIDANA WARGA NEGARA MALAYSIA DALAM BERINTERAKSI DI LEMBAGA PERMASYARAKATAN KELAS II A PEKANBARU - Aditiya Tri Mahfudi; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Indonesia, nowadays, is facing a large challenge of multinational criminalization. These cases are affected from the geographical condition of Indonesia and the large numbers of Indonesia civilizations which make any kinds of criminalization are easy to enter this country. Riau, especially, since this province is directly adjacent with Malaysia, Riau province becomes a strategic location for black markets and illegal transit shipments before they are sent to another regions in Indonesia. Until November 2014, there are five Malaysian prisoners in the Public Prison Class II A of Pekanbaru and they have to make any interactions with the other prisoners or the prison officers. The goal of this research is to analyze the communication patterns and to identify the verbal and nonverbal communication of the Malaysia prisoners in the Public Prison Class II A of Pekanbaru.This research used qualitative methode by phenomenological approach. The subject of research is 5 who represent Community member of ME&ART selected use technique of purposive. Data obtained through participant observation, in-depth interview, and documentation. This research use technique analyse data of interaktif by using data collecting technique, data discount, presentation of data and withdrawal of conclusion.The results of this research are showed that the communication patterns of the Malaysia prisoners are divided into two; the first one is internal communication pattern which uses all channels outline. In this pattern, they can make any interaction and it will influence each other. The second one is Y outline. In this outline, they need a translator to interpret their language. In daily interaction, they use verbal communication in Malay or Chinese with nonverbal communication such as facial, gestural, and postural message.Keywords: communication patterns, verbal and nonverbal communication, prisoners, public prison of Pekanbaru Mahasiswa Jurusan Ilmu Komunikasi angkatan 2009